2020
DOI: 10.1038/s41467-019-13888-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into transcription factor cooperativity and its impact on protein-phenotype interactions

Abstract: Recent high-throughput transcription factor (TF) binding assays revealed that TF cooperativity is a widespread phenomenon. However, a global mechanistic and functional understanding of TF cooperativity is still lacking. To address this, here we introduce a statistical learning framework that provides structural insight into TF cooperativity and its functional consequences based on next generation sequencing data. We identify DNA shape as driver for cooperativity, with a particularly strong effect for Forkhead-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 68 publications
2
61
0
Order By: Relevance
“…The results of recent high-throughput binding assays revealed that transcriptional factor cooperativity is a common cellular phenomenon, 43 which has greatly enhanced our understanding of the interplay between transcription factors. As previously discussed, TEAD4 interacts with TCF4 to form a complex for cobind target genes.…”
Section: Cooperation With Transcription Factorsmentioning
confidence: 99%
“…The results of recent high-throughput binding assays revealed that transcriptional factor cooperativity is a common cellular phenomenon, 43 which has greatly enhanced our understanding of the interplay between transcription factors. As previously discussed, TEAD4 interacts with TCF4 to form a complex for cobind target genes.…”
Section: Cooperation With Transcription Factorsmentioning
confidence: 99%
“…4(c) and 4(f) show that the synthetic circuit is not needed if NK cells are stimulated for less than three hours due to the time delay in transcription and translation. Studies have demonstrated that modulating transcription 80,81 can enhance the rate of protein production. With this knowledge at hand, we alter key parameters that may increase RNA production.…”
Section: Resultsmentioning
confidence: 99%
“…The previous model generates the heterodimeric motif based on separated predictive spacing length and orientation of the monomeric motif pair. Such a synthesis approach has some substantial limitations, since most of TF-TF pairs' cooperatively bound sits involves more than one orientation and various spacing preferences [14,16]. By contrast, DeepMotifSyn generates and scores heterodimeric motif candidates with all potential orientations and spacing preferences (see Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…ChIP-seq, ChIP-exo, and ChIP-nexus) have been developed to detect transcriptions factor binding sites (TFBSs) in various cell types and tissues, while some TFBSs do not have any strong-match motif [7,8,9,10,11]. Several studies have revealed that cooperative TF pairs can function as heterodimers for binding onto the composite DNA motif to regulate gene expression [12,13,14,15,16,17]. Therefore, characterizing TF interactions and the corresponding heterodimeric DNA motifs are essential for understanding the function of non-coding DNA in gene regulation.…”
Section: Introductionmentioning
confidence: 99%